Deep structure and metallogeny of the North Onega synclinorium (Republic of Karelia, Russia): correlation of geological and seismic data - N. Sharov; V.S. Kulikov; E.V. Isanina; G. Drogitskaya; V.I. Kazanskiy (Геофизический журнал, 2013)
The goal of the deep structural study of the North Onega synclinorium, based on correlation of geological and seismic data, is to establish the relation of its surface structure and ore deposits to local heterogeneities of the crust and the crust-mantle interface. ECWM sections characterize geospace both statistically (position and number of boundaries, fault zones and mosaicity) and dynamically (stressed and rigid state of contacts and fracturing). Seismic parameters are shown to be related to the geological structure of individual crustal blocks. The deposits have been found to be spatially related to the elevated thickness of the underplating layer, where the main differentia-tion of mantle magmatic melts, which resulted in the separation of fluid and ore phases, probably occurred in the Palaeoproterozoic. It created favorable conditions for the subsequent intrusion of metal-enriched magmatic melts into upper crustal levels.